Natural Course of Co‐Occurring PTSD and Alcohol Use Disorder Among Recent Combat Veterans. Issue 3 (6th June 2017) - Possemato, Kyle; Maisto, Stephen A.; Wade, Michael; Barrie, Kimberly; Johnson, Emily M.; Ouimette, Paige C.
Abstract : Posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD) commonly co‐occur in veterans, yet little is known about the longitudinal course of PTSD and drinking in comorbid populations. This study assessed the natural course of daily alcohol consumption and weekly changes in PTSD symptoms in 112 recent combat veterans over the course of 11 months. Latent class growth mixture modeling was used to classify individuals into distinct classes with similar PTSD symptom and alcohol use growth trajectories. We then investigated theorized predictors of class membership including sociodemographics; pre‐, peri‐, and postdeployment factors; coping; symptom severity; and number of mental health/substance use appointments attended. Results revealed that most participants had severe and nonremitting PTSD. Trajectories for alcohol use included gradual and drastic declines, and chronic low‐level drinking. The use of behavioral health services (odds ratio = 2.47) and fewer current stressors (odds ratio = 0.42) predicted AUD remission. Because little variation was observed in the PTSD course, our study did not observe coordinated fluctuations of PTSD symptoms and heavy drinking. Our findings suggest that treatment impacts the course of AUD and that recent combat veterans who do not seek PTSD treatment may have chronic and severe PTSD symptoms.